2021
DOI: 10.1101/2021.09.16.460678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic Characterization of Isolated Arabidopsis Clathrin-Coated Vesicles Reveals Evolutionarily Conserved and Plant Specific Components

Abstract: In eukaryotes, clathrin-coated vesicles (CCVs) facilitate the internalization of material from the cell surface as well as the movement of cargo in post-Golgi trafficking pathways. This diversity of functions is partially provided by multiple monomeric and multimeric clathrin adaptor complexes that provide compartment and cargo selectivity. The adaptor-protein AP-1 complex operates as part of the secretory pathway at the trans-Golgi network, while the AP-2 complex and the TPLATE complex (TPC) jointly operate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 199 publications
(212 reference statements)
0
25
0
Order By: Relevance
“…The depletion of TPLATE was observed in parallel with a similar lack of enrichment of dynamin-related protein 1c (DRP1c), which functions outside the CCV (14). Critically, these finding have recently been confirmed by mass spectrometry of purified CCV samples in which none of the TPC members were found to be significantly enriched in CCVs (15). The absence of TPLATE enrichment in purified CCVs demonstrates that TPLATE is not incorporated within CCV structures as previously predicted, and when combined with the early departure of TPLATE from CCVs (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The depletion of TPLATE was observed in parallel with a similar lack of enrichment of dynamin-related protein 1c (DRP1c), which functions outside the CCV (14). Critically, these finding have recently been confirmed by mass spectrometry of purified CCV samples in which none of the TPC members were found to be significantly enriched in CCVs (15). The absence of TPLATE enrichment in purified CCVs demonstrates that TPLATE is not incorporated within CCV structures as previously predicted, and when combined with the early departure of TPLATE from CCVs (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…1 D and E). Notably, this result has been confirmed by mass spectrometry of purified CCVs, in which it was found that all members of the TCP failed to show any strong enrichment in CCVs (15). Thirdly, to increase our spatial resolution of live CME events, we used SIM.…”
Section: Discussionmentioning
confidence: 73%
“…By using the same sample preparation for biochemically isolated CCVs, we could directly compare them to specific CCV populations visualized inside cells. While we found that there were small differences in the sizes of endocytic and isolated CCVs, this is likely due to the fact that the isolated CCV preparations from whole cell lysates contain a mixture of CCVs derived from different origins -clathrin-mediated endocytosis and the early endosome/trans-Golgi network (22,27,28). We then validated our high throughput pseudo 3D analysis by applying it to metal replicas of unroofed cells carrying an inducible loss of endocytic membrane bending.…”
Section: Discussionmentioning
confidence: 77%
“…This raises out another question: how do AP1 and AP4 distinguish their specific cargoes on TGN/EE in two independent pathways or whether they function in parallel with overlapping cargos? In another finding using tandem mass spectrometry analysis, only AP1, AP2, and AP4 subunits were identified in enriched CCV proteome in Arabidopsis (Dahhan et al, 2021). It is possible that other accessory proteins might be involved to assemble as coatomer with similar function as the clathrin cage in AP3 vesicles.…”
Section: Discussionmentioning
confidence: 94%